The legacy of Sheikh Ma'roof al-Nudi from the perspective of Sayyid Ahmad Faiz al-Barzanji - Aziz, L.Dr. Hamid Muhammad Amin (Sulaimani Journal for Humanities, 2024)
This research examines the legacy of Sheikh Ma'ruf al-Nawdhi al-Barzanji from the perspective of the eminent scholar Sayyid Ahmad Faiz al-Barzanji. Al-Nawdhi left behind a vast intellectual wealth for scholars and researchers, and many scholars dedicated themselves to serving his legacy. Among the most prominent figures who commented on and annotated al-Nawdhi's works was Sayyid Ahmad Faiz. These two scholars shared familial and spiritual ties, as well as a scholarly relationship. Sayyid Ahmad Faiz wrote commentaries on two of al-Nawdhi's theological treatises: the poem "al-Fara'id" (twice) and the poem "al-Durra al-Farida." He also wrote a commentary on a poem by al-Nawdhi on the virtues of the Ahl al-Bayt (the Prophet's family) entitled "Rawd al-Zahr," and a poem on rhetoric entitled "Fath al-Rahman," on which he also wrote an annotations. This study aims to highlight Ahmad Faiz's contributions to these works explaining al-Nawdhi's legacy, providing a brief overview of each.
Keywords: AlNawdhi; AlBarzanji; Sheikh Maarouf; Ahmed Faiz; AlKalzardi; Scientific Systems